A dual-responsive doxorubicin–indoximod conjugate for programmed chemoimmunotherapy. Issue 7 (15th June 2022) - Yang, Zhaoxuan; Huang, Jiaqi; Lin, Yaying; Luo, Xiangjie; Lin, Haojin; Lin, Hongyu; Gao, Jinhao
Abstract : A dual-responsive doxorubicin–indoximod conjugate was developed, which allows for sequential on-demand release of doxorubicin and indoximod for programmed chemoimmunotherapy. Abstract : Herein we report a dual-responsive doxorubicin–indoximod conjugate (DOXIND) for programmed chemoimmunotherapy. This conjugate is able to release doxorubicin and indoximod upon exposure to appropriate stimuli for synergistic chemotherapy and immunotherapy, respectively. We demonstrate its promoting effects on immune response and inhibiting effects on tumor growth through a series of in vitro and in vivo experiments.